Ischemia-Modified Albumin as a Marker of Acute Coronary Syndrome: The Case for Revising the Concept of "N-Terminal Modification" to "Fatty Acid Occupation" of Albumin. (5th March 2017) - Oran, Ismail; Oran, Bulent
Abstract : Ischemia-modified albumin (IMA) is assumed "N-terminal modified" albumin which is generated immediately following myocardial ischemia. The diagnosis of IMA is based on reduced cobalt binding affinity to albumin which is attributed mainly to incapability of cobalt to bind at albumin's modified N-terminus. Although the albumin cobalt binding test was accepted as a potentially powerful marker for discriminating acute coronary syndrome from nonischemic chest pain, its usefulness has been brought into question in recent years. Patients with acutely ischemic myocardium exhibit a rapid increase in serum levels of fatty acids (FAs). Almost all released FAs are strongly bound to albumin which create conformational changes in the protein with resultant reduced cobalt binding affinity. There is a clear metabolic and temporal relationship between IMA measured via albumin cobalt binding testing and serum levels of FAs. In line with what has been suggested recently in the literature, we conclude that a shift from the concept of "N-terminal modified" to "FA-occupied" albumin is required, as this better describes IMA in patients with acute coronary syndrome. We also offer "oxidation modified albumin, OMA, " which is conceptually different from the "FA-occupied" IMA, to describe modification of albumin in chronic disease associated with increased oxidative stress.